Characterisation of magnetic field effects through sensitive spectroscopic measurement - Murton, P (2024)
Avian magnetoreception, the ability of birds to perceive and navigate using the Earth’s magnetic field, is a phenomenon whose basis has intrigued scientists for decades. One leading hypothesis is the radical pair mechanism (RPM) which has been proposed as a possible magneto-sensing mechanism in biological systems such as the magnetoreception of night migratory songbirds (Chapter 1). In particular, the retinal cryptochrome 4a proteins of these birds are believed to exhibit the key features necessary for magnetosensing. That is, the formation of photoinduced radical pairs (RPs) whose interaction with magnetic fields, due to their quantum spin dynamics, causes variations in the yields of their photoproducts, known as a magnetic field effect (MFE). The quantum mechanics of spin, the RPM and its manifestation in cryptochrome 4a proteins is introduced in Chapter 2.